Physiological and neuromuscular response to two HIIT protocols in resistance corridors (Revista horizonte, 2021)
Since a growing body of evidence points to mean training intensity over a season as a key factor to performance improvements, and there is wide evidence of the benefits of high-intensity intermittent training (HIIT) for endurance athletes, coaches need further information about the acute impact of typical HIIT workouts on endurance runners.Objective: To compare the physiological strain and muscular performance parameters of endurance runners during two HIIT workouts by determining whether a typical HIIT for endurance runners (10x400 m) leads to a similar impact as a HIIT protocol (40x100 m) that increases the average training pace despite maintaining the same training volume.Methods: Eighteen endurance runners performed 2 HIITs. Metabolic (blood lactate [BLa], blood ammonia [BAmm]), neuromuscular (countermovement jump [CMJ], handgrip strength test [HS]), and physiological responses were monitored during both protocols. Results: No significant differences between HIITs were found for BLa_1 min post-test, BAmm, HS and HRpeak. Significant differences were found in fatigue-induced changes in CMJ performance (âˆ’0.36 cm in 40x100 m; +1.48 cm in 10x400 m), and in average pace (P